Biological features of different breeds of goats - Karban, Y. (Scientific Progress & Innovations, 2024)
The work presents the results of biological, morphometric, and ethological studies. The main biological and economically beneficial characteristics of goats of various breeds are considered. The study was conducted on 3 groups of goats of the Zaanen, Alpine and Anglo-Nubian breeds at the age of 3–4 years. The Zaanen goats studied in this study served as a control group, as they are one of the first breeds introduced to the territory of Ukraine and are very popular among the population due to their milk productivity. Depending on the biological features, goats are divided into different areas of productivity: milk, meat, wool and leather. The evaluation of biological features of goats was carried out according to the following indicators: daily rhythms of behavior, biological, morphometric, to determine body parameters. It was established that the behavior of female goats in the pasture-stall system varies depending on the breed. So the animals of the Zaanen breed turned out to be more static, they stood for a longer period. Animals of Alpine and Nubian breeds were noted to be more mobile, respectively by 21.0 % (p<0.001) and 18.5 % (p<0.001). The time of fodder consumption in the stable was maximum in Zaanen and Alpine breeds. The minimum duration of mastication was established in animals of the Zaanen breed, while in the Anglo-Nubian and Alpine breeds this process lasted longer by 17.3 % (p<0.001) and 12.4 % (p<0.001), respectively. The smallest amount of time spent on water consumption was observed in animals of the Zaanen breed, and in the Anglo-Nubian and Alpine breeds, the data were higher by 15.0 % (p<0.01) and 25.0 % (p<0.001), respectively. A probable difference in body temperature of animals of different breeds was revealed, where the minimum indicator (p<0.01) compared to Zaanen goats was in the Anglo-Nubian breed in the winter period. Anglo-Nubians had the lowest breathing rate in summer (p<0.01), and pulse rate in spring (p<0.01). In the alpine breed, the pulse frequency was minimal in the summer (p<0.01) and autumn (p<0.05) periods. The study of the features of the body structure of female goats established that the height at the withers compared to Zaanen animals was maximum in Anglo-Nubian goats by 5.8 % (р<0.01), minimum in Alpine Tvanins by 3.9 % (р<0.05) . The height at the sacrum was higher in alpine goats by 15.4 % (p<0.001) and in Anglo-Nubian goats by 2.6 % (p<0.05) compared to Zaanen breeds. It was found that female goats of the Anglo-Nubian breed of goats exceeded other studied animals in terms of chest depth (p<0.001), oblique body length (p<0.001), chest girth (p<0.001), body weight (p<0.01).